PERKEMBANGAN PEMIKIRAN, ILMU, DAN DINAMIKA PERADABAN MODERN - Lina Desriana Pratiwi; Nur Aisyatul Badriyah; Debi Setiawati (Yayasan Literasi Sains Indonesia, 2022)
Analysis of the development of thought, science, and the dynamics of modern civilization which describes how modern civilization develops due to new thoughts and sciences. There are several studies in this article, namely thought, progress, decline, science, and civilization. In outlining this discussion there are several things related to the importance of thought and science in driving modern civilization. This research uses the library method with a qualitative approach, conducted at the Budi Utomo Institute of Teacher Training and Science Malang. The purpose of this study is to determine the relationship between the development of thought and science and the dynamics of modern civilization. Data was collected by reviewing related books, literature, records, and various reports. Data analysis uses an interactive analysis model which includes data collection, data reduction, data presentation and drawing conclusions. The results of the study show that thought and knowledge are very influential in the progress of modern human civilization.